True-to-scale DNA-density maps correlate with major accessibility differences between active and inactive chromatin - Gelléri, Márton; Chen, Shih-Ya; Hübner, Barbara; Neumann, Jan; Kröger, Ole; Sadlo, Filip; Imhoff, Jorg; Hendzel, Michael J.; Cremer, Marion; Cremer, Thomas; Strickfaden, Hilmar; Cremer, Christoph (Cell reports, 2023)
Chromatin compaction differences may have a strong impact on accessibility of individual macromolecules and macromolecular assemblies to their DNA target sites. Estimates based on fluorescence microscopy with conventional resolution, however, suggest only modest compaction differences (∼2-10×) between the active nuclear compartment (ANC) and inactive nuclear compartment (INC). Here, we present maps of nuclear landscapes with true-to-scale DNA densities, ranging from <5 to >300 Mbp/μm3. Maps are generated from individual human and mouse cell nuclei with single-molecule localization microscopy at ∼20 nm lateral and ∼100 nm axial optical resolution and are supplemented by electron spectroscopic imaging. Microinjection of fluorescent nanobeads with sizes corresponding to macromolecular assemblies for transcription into nuclei of living cells demonstrates their localization and movements within the ANC and exclusion from the INC.